The cybrarian's web : an A-Z guide to 101 free Web 2.0 tools and other resources - Peltier-Davis, Cheryl Ann (Facet Publishing, 2012)
This is a remarkable field guide to the best of free Web 2.0 tools and their practical applications in libraries and information centres